Efektivitas Program Kerja Sama Unaids-Indonesia Tentang HIV/AIDS Melalui Media Sosial Instagram @Tanya Marlo - Andina Mustika Ayu; Alessandro Kurniawan Ulung (Jurnal Netnografi Komunikasi, 2023)
Abstract - An international organization dealing with issues related to HIV/AIDS, The Joint United Program on HIV/AIDS (UNAIDS) under the auspices of the United Nations, cooperates with the provincial government of DKI Jakart. The collaboration through the fast track cities agenda is to achieve an understanding of the status of HIV/AIDS through the Tanya Marlo application. Because Tanya Marlo is still in a pilot project, researchers are testing the effectiveness of this program, whether this has an effect on increasing the expected target achievement. HIV/AIDS is a global problem that will continue to occur, and if it is not handled together, the consequences will significantly affect the order of life in the international community. Thus, solving cases must also use all forms of approaches in today's modern era such as the use of online communication media which can reach targets more quickly and at a more affordable cost. From the data that has been processed by researchers, the UNAIDS-Indonesia collaboration program through the socialization of Tanya Marlo in understanding HIV/AIDS status in key populations in DKI Jakarta has been effectively carried out.